Social knowledge : using social media to know what you know - Girard, John P., 1961-; Girard, JoAnn L. (Hershey, PA : Information Science Reference, 2011)
'This book provides relevant theoretical frameworks, latest empirical research findings, and practitioners' best practices social knowledge, for improving understanding of the strategic role of social knowledge in business, government, or non-profit sectors'--Provided by publisher.
Social knowledge in action -- Social learning from the inside out : the creation and sharing of knowledge from the mind/brain perspective / David Bennet, Alex Bennet -- Measuring the impact of social media : connection, communication, and collaboration / Kimiz Dalkir -- Challenging our assumptions : making sense of the sharing of social knowledge / Suzanne Roff-Wexler, Loretta L. Donovan, Salvatore Rasa -- Social knowledge case study : innovation linked to the collaborative socialization of knowledge / Cindy Gordon -- Social knowledge in the Japanese firm / Benjamin Hentschel, Parissa Haghirian -- Cultural aspects of social knowledge -- Cultural barriers to organizational social media adoption / Andrew Miller -- Organizational culture : a pillar for knowledge management / Paul J. McBride -- Social leadership : exploring social media and the military : a new leadership tool / Scott Campbell Mackintosh -- Foundations of cross-cultural knowledge management / Nhu T. B Nguyen, Katsuhiro Umemoto -- Social knowledge tools, techniques, and technologies -- Becoming a blogger : a social knowledge experiment / Stefania Mariano -- Encouraging participation in virtual communities of practice within the United States air force / Nick Bowersox -- Social knowledge workspace / Jagdish K Vasishtha -- Sharing scientific and social knowledge in a performance oriented industry : an evaluation model / Haris Papoutsakis -- Social knowledge : the technology behind / Chethan. M, Mohan Ramanathan -- Empowering social knowledge with information technology : technological and cultural issues convergence / Fjodor Ruzic.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Organizational learning; Social networks; Knowledge management